Lieb–Robinson bounds for open quantum systems with long-ranged interactions. (24th September 2019) - Sweke, Ryan; Eisert, Jens; Kastner, Michael
Abstract: We state and prove four types of Lieb–Robinson bounds valid for many-body open quantum systems with power law decaying interactions undergoing out of equilibrium dynamics. We also provide an introductory and self-contained discussion of the setting and tools necessary to prove these results. The results found here apply to physical systems in which both long-ranged interactions and dissipation are present, as commonly encountered in certain quantum simulators, such as Rydberg systems or Coulomb crystals formed by ions.